Criteria, Indicators and Levels of Preparedness of Future Border Guard Officers to the Location of Non-Standard Situations at Checkpoints Across the State Border - Olha Lemeshko (Pedagogical Discourse, 2016)
The article deals with the theoretical bases of preparedness of the future border guard officers to the location of non-standard situations at checkpoints across the state border. The conflict ability within the conflict formation preparedness of the future border guard officers in the performance of official duties at checkpoints across the state border has been analyzed. The theoretical approaches of scientists to the definition of the terms «criterion», «index» and «level» have been generalized. The criteria (personal and motivational, cognitive and informative and active and effective) and their indices to achieve good results in increasing the level of the researched concept have been determined. The level of preparedness (low, medium and high) of future border guard officers to the localization of non-standard situations at checkpoints across the state border have been given taking into account its internal structure. The preparedness of the future border guard officers to localization of non-standard situations at checkpoints across the state border depends on the motivation of educational activity. Personal and motivational criterion characterizes the motivation and direction of future border guard officers to study the principles of non-standard situations, peculiarities of localization of non-standard situations at checkpoints across the state border, their attitude to the formation of preparedness for localization of non-standard situations. Cognitive and informative criterion characterizes the body of knowledge about the theory and practice of localization of non-standard situations at checkpoints across the state border. Active and effective criterion deals with skills of future border guard officers to use knowledge on physical effects to solve non-standard situations.Key words: preparedness, future border guard officers, criteria, indicators, levels, non-standard situation, localization.